Arabidopsis thaliana model system reveals a continuum of responses to root endophyte colonization - Mandyam, Keerthi G.; Roe, Judith; Jumpponen, Ari M. (My University, 2013)
We surveyed the non-mycorrhizal model plant Arabidopsis thaliana microscopically for its ability to form dark septate endophyte (DSE) symbioses in field, greenhouse, and laboratory studies. The laboratory studies were also used to estimate host growth responses to 34 Periconia macrospinosa and four Microdochium sp. isolates. Consistent with broad host range observed in previous experiments, field-, greenhouse-, and laboratory-grown A. thaliana were colonized by melanized inter- and intracellular hyphae and microsclerotia or chlamydospores indicative of DSE symbiosis. Host responses to colonization were variable and depended on the host ecotype. On average, two A. thaliana accessions (Col-0 and Cvi-0) responded negatively, whereas one (Kin-1) was unresponsive, a conclusion consistent with our previous analyses with forbs native to the field site where the fungi originate. Despite the average negative responses, examples of positive responses were also observed, a conclusion also congruent with earlier studies. Our results suggest that A. thaliana has potential as a model for more detailed dissection of the DSE symbiosis. Furthermore, our data suggest that host responses are controlled by variability in the host and endophyte genotypes.
Keywords: Dark septate endophytes (DSE); Microdochium sp.; Mutualism-parasitism continuum; Periconia macrospinosa; Arabidopsis thaliana